2020
DOI: 10.1186/s12872-020-01630-x
|View full text |Cite
|
Sign up to set email alerts
|

N-terminal pro-B-type natriuretic peptide as a prognostic indicator for 30-day mortality following out-of-hospital cardiac arrest: a prospective observational study

Abstract: Background Early risk stratification applying cardiac biomarkers may prove useful in sudden cardiac arrest patients. We investigated the prognostic utility of early-on levels of high sensitivity cardiac troponin-T (hs-cTnT), copeptin and N-terminal pro-B-type natriuretic peptide (NT-proBNP) in patients with out-of-hospital cardiac arrest (OHCA). Methods We conducted a prospective observational unicenter study, including patients with OHCA of assumed cardiac origin from … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Most of the studies were conducted in Asia (63 studies, 53%). Only 22 studies (19%) had blood samples collected in the prehospital setting, and only six studies (5%) had intra‐arrest blood samples collected by paramedics in the prehospital setting 12–14,20,82,83 . Only three studies (3%) enrolled any pediatric patients 24,90,114 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the studies were conducted in Asia (63 studies, 53%). Only 22 studies (19%) had blood samples collected in the prehospital setting, and only six studies (5%) had intra‐arrest blood samples collected by paramedics in the prehospital setting 12–14,20,82,83 . Only three studies (3%) enrolled any pediatric patients 24,90,114 .…”
Section: Resultsmentioning
confidence: 99%
“…The search strategy identified a total of 11,834 records, of which 6914 were non‐duplicates. After applying all inclusion and exclusion criteria, 118 studies were included in the scoping review, as shown in Figure 1 11–128 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous prospective study, when 30-day mortality was the measured outcome, NT-pro BNP was high in non-survivors. However, it was confirmed that it was not a significant factor in multivariate analysis [29]. In another prior study, the NT-pro BNP levels of 155 OHCA shockable rhythm patients were measured after 24 h and provided improved risk assessment of poor outcomes after one year, on top of the established risk indices [30].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we analysed activated Factor XI-antithrombin (FXIa-AT) complex, activated Factor IX-antithrombin (FIXa-AT) complex and TAT complex as a measure of coagulation activation. The primary aim of our study was to evaluate the independent prognostic utility of these three coagulation markers in a previously described population of OHCA patients with both shockable-and non-shockable heart rhythm [11]. As a second aim, this study was performed to improve our understanding of the pathophysiology related to coagulation activation during cardiac arrest, including both the intrinsic-and the extrinsic pathway.…”
Section: Introductionmentioning
confidence: 99%